Website Development of Sarwa Adem Mulya Cooperative as a Digital Platform for Promotion and Education of Ruminant Livestock Farmers: Pengembangan Website Koperasi Sarwa Adem Mulya sebagai Sarana Promosi dan Edukasi Digital Peternak Ruminansia - M Syauqi Haris; Risqy Siwi Pradini; Mochammad Anshori (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Koperasi Multi Pihak Sarwa Adem Mulya is a ruminant livestock-based cooperative located in Malang, East Java. The cooperative has great potential for business development but faces challenges in utilizing information technology, particularly in digital promotion and education. This community service activity aims to develop a cooperative website using the WordPress-based Content Management System (CMS) to strengthen its position in the digital era. The implementation method includes needs analysis, website design and development, training for cooperative administrators, as well as monitoring and evaluation of website usage effectiveness. The developed website features key components such as a cooperative profile, livestock product catalog, educational modules, and basic e-commerce integration. The results show that the website has been successfully implemented through the cooperative's official domain, and administrators are able to independently manage the content. Furthermore, an increase in digital literacy among administrators was observed based on pre-test and post-test evaluations. This website is expected to serve as a sustainable medium for promotion and education, and as a replicable model for the digitalization of other livestock cooperatives.